BIBB international - strategy paper on the internationlisation of German vocational education and training - Dybowski, Gisela [Verfasser]; Hanf, Georg [Verfasser]; Walter, Matthias [Verfasser] (My University, 2007)
"The process of internatiolisation has gathered pace in recent years, spreading through one area of society after another and posing new challanges, not least for vocational education and training (VET). The growing globalisation of the economy and the rapid process of European integration towards a single market for education and employment have given rise to a radically new situation. National VET systems are caught in a cross-current between the imperative of international competition and the necessity for cross-border cooperation. At the same time, there are increasingly stringent requirements for the planning of VET to embrace a European and an international outlook. The paper explains the action to be taken by the Federal Institute for Vocational Education and Training (BIBB) in response to these developments." (BIBB)

Der Internationalisierungprozess hat in den vergangenen Jahren an Fahrt gewonnen und dehnt sich auf immer mehr Bereiche der Gesellschaft aus. Die wachsende Globalisierung der Wirtschaft und das schnelle Zusammenwachsen Europas zu einem Binnenmarkt für Bildung und Beschäftigung stellen auch für die berufliche Bildung eine Herausforderung dar. Der Druck auf die nationalen Bildungssysteme, sich dem internationalen Wettbewerb zu stellen und die Notwendigkeit zu grenzüberschreitender Kooperation erfordern von der Berufsbildungspolitik eine verstärkte europäische und internationale Perspektive. Der vorliegende Beitrag beschreibt die Strategie des Bundesinstituts für Berufsbildung (BIBB), diesen Entwicklungen Rechnung zu tragen. (BIBB2)
Keywords: I 1 Internationale Berufsbildung; S 2.3 Berufsbildungspolitik; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Berufsbildung; Internationalisierung; Internationale Zusammenarbeit; Europäische Integration; Berufsbildungspolitik; Strategie; Bundesinstitut für Berufsbildung